Association between the C-reactive protein/albumin ratio and prognosis in patients with oral squamous cell carcinoma - Kenji Yamagata; Satoshi Fukuzawa; Naomi Ishibashi-Kanno; Fumihiko Uchida; Hiroki Bukawa (Scientific Reports, 2021)
Abstract The systemic inflammatory response is known to be associated with poor outcomes in patients with various types of cancer. The C-reactive protein (CRP)/albumin (Alb) ratio (CAR) has been reported as a novel inflammation-based prognostic marker. We have evaluated the prognostic value of inflammatory markers for patients with oral squamous cell carcinoma (OSCC). The study population included 205 patients treated with OSCC between 2013 and 2018. The primary predictor variable was the inflammatory markers. The primary outcome variable was overall survival (OS). Univariate and multivariate analyses were performed using a Cox proportional hazards model to identify independent prognostic factors. The CAR had the highest area under the curve (AUC) values compared with other markers in the receiver operating characteristic (ROC) curve analysis. The cutoff value for CAR was 0.032 (AUC 0.693, P < 0.001). There was a significant difference in OS when patients were stratified according to CAR, with 79.1% for CAR < 0.032 and 35% for CAR ≥ 0.032 (P < 0.001). Cox multivariate analysis identified independent predictive factors for OS: age (hazard ratio [HR] 2.155, 95% confidence interval [CI] 1.262–3.682; P = 0.005), stage (HR 3.031, 95% CI 1.576–5.827; P = 0.001), and CAR (HR 2.859, 95% CI 1.667–4.904; P < 0.001). CAR (≥ 0.032 vs. < 0.032) is a good prognostic marker in patients with OSCC in terms of age and stage.